The Study of Antiallergic Activity of the Phytocollection of “Phytoallergoderm” - Bakhtiyor Imamaliev1, Ziyoda Fayzieva1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The antiallergic activity of “Phytoallergoderm” phytocollection was studied, which was recommended fortopical treatment of a topic dermatitis, on the model of allergic contact dermatitis, caused by skin applicationof turpentine. The following drugs were used as comparison: antihistamine “Psilo-Balsam” gel, manufacturer:OJSC “Nizhpharm” Russia; glucocorticoid (topical steroid) “Dermoveit” cream 0.05%, manufacturer:“Glaxo Smith Kline Pharmaceuticals SA” Poland; zinc product “Zinc” ointment, manufacturer: NPP“Radiks” Uzbekistan.During the experiment, it was found that the test drug has a reliable anti-allergic activity, which is clearlycaused of decrease in total allergic reactions, in the reduction of recovery time and in a decrease in thedynamics of the severity of allergic reactions. Also, the study of antiallergic activity showed that the testdrug has a comparable antiallergic activity with the etalon synthetic drug.The foregoing indicates the presence of a reliable anti-allergic activity of the phytocollection“Phytoallergoderm”, which is comparable to reference synthetic preparations.